Abceso hepatico amebiano en pediatria - Echeverria, Victor (Revista Universidad de Guayaquil, 1987)
Histolytic amoeba infection affects all communities in the universe, with prevalence in tropical climates, with a large percentage of asymptomatic carriers eliminating cysts that infect healthy people. Reviewing the statistical files of the Alejandro Mann Children’s Hospital in the city of Guayaquil, which provides outpatient care to approximately an average of 147,464 per year, with an average annual hospitalization of 3,096 of a child population from all regions of the country; Of the positive coproparasitoscopic diagnoses we found a high incidence of intestinal polyparasitism. Amoebiasis ranks third after ascariasis and giardiasis. Of them, 65% were healthy carriers, with a prevalence in school age, producing predominantly diarrhea, abdominal pain and moderate anemia in the symptomatic ones.